Influência dos resíduos do beneficiamento de caulim e cobre nas propriedades físicas, mecânica de impacto e flamabilidade dos compósitos de matriz poliéster isoftálica - SOUSA, Ana Paula Souza de (2022)
Industrial activities in the world generate different types of waste with different chemical and physical properties, which causes a concern with the mass production of these materials. Thus, there is a great interest in the reuse of industrial waste in composite materials due to the good performance that this combination presents. In this sense, this work aims to analyze the influence of kaolin and copper sulphide industrial waste as filler in polyester matrix composites from the analysis of physical, mechanical and flammability characterizations. For the manufacture of the materials, the manual hand lay-up method was used, in which the isophthalic unsaturated polyester resin was used with the use of an accelerator in the proportion of 1,5 % v/v and initiator in the proportion of 1 % v/v. For the physical and flammability tests, the copper residue was inserted into the matrix in the mass fractions of 10 %, 20 %, 30 %, 40 % and 50 % and the kaolin residue in the fractions of 10 %, 20 %, 30 % and 40 %, while for the impact test the residues were inserted in the fractions of 10 % and 20 %, in which a 100 mesh Tyler series sieve was used. After making the materials, physical tests were carried out (ASTM D 1984-92), impact resistance (ASTM D 6110-18), analysis of the fracture surface by means of scanning electron microscopy and horizontal flammability (ASTM D 635-18). In the results obtained for water absorption and apparent porosity, all composites showed lower values than those of the full matrix, highlighting the materials with 40 % kaolin residue and 30 % copper residue. For the impact tests, the results remained stable, as all materials showed strength values close to the full matrix (19,38 kJ/m2), especially the composites with 20 % kaolin residue (21,20 kJ/m2) and 10 % copper residue (21,20 kJ/m2). In the analysis of fracture surfaces, it was noted the presence of failure mechanisms such as voids, bubbles and agglomerates and the materials showed good dispersion of residues in the matrix. In the flammability test, all materials had satisfactory results since they showed lower ropagation rates than required by the standard and by CONTRAN-14 (National Traffic Council), especially the composites with 10 % kaolin and copper that showed reduction of 85,49 %.